Working beyond retirement age: a systematic review - Minhat, Halimatus Sakdiah; Suwanmanee, Suttama (Faculty of Medicine and Health Sciences, UPM, 2023)
Introduction: Population ageing brings along various crucial implications, with working beyond retirement age is one of the economics implications of ageing. Realizing the increasing demand and concern to accommodate older adults into the workforce, this review was conducted to develop better understanding on the factors associated with post-retirement employment among older adults aged 50 years and older. Methods: Using Scopus, ScienceDirect and PubMed databases, related articles between January 2017 and June 2021 were thoroughly searched using combination of keywords and screened according to the predetermined eligibility criteria. Post-retirement employment was defined as employment of older adults aged 50 years old and above beyond retirement age or re-employment of retired older adults, either from compulsory or voluntary retirement. All observational, qualitative, mixed methods and experimental studies were included in the screening process. The Crowe Critical Appraisal Tool (CCAT) was used to assess the quality of included articles. Results: A total of 12 articles included for review, with seven articles rated as high-quality. The review had successfully identified 10 factors associated with working beyond retirement age among older adults. Having good health status and being male gender were the commonest factors influencing the decision to work beyond retirement age, followed by level of education, financial commitment/ reasons, and work characteristics. Conclusion: The findings of this review provide a crucial insight and foundation towards addressing the unique needs of older workers in the employment policy.